Long-term outcomes of a randomized clinical trial of supervised exercise, percutaneous transluminal angioplasty or combined treatment for patients with intermittent claudication due to femoropopliteal disease. Issue 1 (20th October 2016) - Mazari, F A K; Khan, J A; Samuel, N; Smith, G; Carradice, D; McCollum, P C; Chetter, I C
Abstract: Background: The aim was to compare the long-term outcomes of percutaneous transluminal angioplasty (PTA), a supervised exercise programme (SEP) and combined treatment (PTA + SEP) in patients with intermittent claudication owing to femoropopliteal disease. Methods: Patients recruited to an RCT comparing these treatments were invited for long-term follow-up from 2010 to 2011. Indicators of limb ischaemia were recorded (ankle : brachial pressure index (ABPI) and treadmill walking distances). Duplex ultrasound imaging was also done. Patients completed Short Form 36 and VascuQol quality-of-life (QoL) questionnaires. Results: Of 178 patients initially recruited to the trial, 139 were alive at the time of follow-up (PTA 46, SEP 47, PTA + SEP 46). Assessments were completed for 111 patients. Median time to follow-up was 5·2 (i.q.r. 3·8–7·4) years. Sixty-nine patients (62·2 per cent) were symptomatic; 18 (16·2 per cent) had experienced a major cardiovascular event since their last follow-up visit. Improvement was observed in ABPI in all groups. QoL outcomes were inconsistent across individual groups. PTA and PTA + SEP groups had a significantly higher ABPI than the SEP group. No significant difference was observed in treadmill walking distances, QoL outcomes, restenosis rates, and new ipsilateral and contralateral lesions on duplex imaging. Patients in all groups required reinterventions (PTA 14, SEP 10, PTA + SEP 6). The total number of reinterventions was higher after PTA (29) compared with SEP (17) and PTA + SEP (9), but failed to reach statistical significance. Conclusion: PTA, SEP and combined treatment were equally effective long-term treatment options for patients with claudication owing to femoropopliteal disease. The addition of a SEP to PTA can reduce the rate of symptomatic restenosis and reintervention. Registration number: NCT00798850 (http://www.clinicaltrials.gov ). Abstract : Informs treatment of claudication